The Role of Connexins in Carcinogenesis: Review of Current Knowledge - Luiza, Kanczuga-koda; Stanislaw, Sulkowski; Mariusz, Koda; Andrzej, Wincewicz; Tadeusz, Rutkowski; Mariola, Moniuszko (Current Signal Transduction Therapy, 2007)
Gap junctional intercellular communication is a mechanism for direct cell-to-cell signaling and is mediated by gap junctions, which consist of transmembrane proteins called connexins. Many physiological roles have been proposed for gap junctions such as maintenance of tissue homeostasis, regulation of tissue development, electrical and metabolic coupling as well as regulation of cellular growth, differentiation and apoptosis. Signaling is especially altered via gap junctions in cancer. Furthermore, these membrane channels are believed to be engaged in metastasis. Involvement of aberrant gap junctional intercellular communication in carcinogenesis and tumor suppressing role of connexin genes has been well documented. However, clear explanation is required for the role of connexins that are localized in intracellular compartment of cancerous cells and participate in apoptosis and metastasis as well. The present review is confined to role of connexins in a cell signaling during carcinogenesis, regulation of apoptosis and involvement in metastasis. Potential role of gap junctions and connexins in therapy of cancers was analyzed, too.
Keywords: carcinogenesis